In vitro capacitation of stallion spermatozoa - Spizziri, Beth Erin, author; Graham, James K., advisor; Bouma, Gerrit, committee member; Bruemmer, Jason, committee member; Seidel, George, committee member (Colorado State University. Libraries, 2010)
Equine in vitro fertilization has resulted in limited success, and progress is hindered due to a lack of understanding the molecular and biochemical events involved in stallion sperm capacitation. As no single test exists to determine if a stallion sperm is capacitated, individual events of capacitation can be monitored to determine if treatments can induce in vitro changes involved in sperm capacitation. In addition, the limited availability of equine oocytes for experimentation has led to the use of heterologous oocyte assays to determine if various sperm treatments to induce sperm capacitation can result in these sperm fertilizing oocytes in vitro. In experiment 1, sperm plasma membrane cholesterol content of sperm was examined after treatment with capacitation inducing agents. Samples treated with methyl-~-cyclodextrin (MBC) exhibited lower (p<0.05) cholesterol content after 3 h incubation (16 μg/108 sperm) than control sperm at Oh (22 μg/108 sperm). Samples preloaded with cholesterol, after incubation with cholesterol-loaded-cyclodextrin (CLC), contained more cholesterol than control sperm (p<0.05). The second experiment was designed to determine if that protein tyrosine phosphorylation, a component of sperm capacitation, occurs under in vitro conditions. Sperm were capacitated in vitro in Modified Whitten's (MW) medium alone or with dilauroylphosphatidylcholine (PC 12; 40 μm), calcium ionophore A23187 (2 μm), or MBC ( 1 μm) for 0, 30, 90, and 180 min, and the amount of protein tyrosine phosphorylaton was assessed. PC 12-treated sperm exhibited the highest amount of protein tyrosine phosphorylation at time Oh. Control sperm exhibited the highest amount of protein tyrosine phosphorylation following a 3 h incubation. Tyrosine phosphorylation was negligible with MBC and calcium ionophore A23187 treatments. The third experiment was designed to adapt detection of protein tyrosine phosphorylation detection of stallion spermatozoa to flow cytometery. When sperm were incubated with nothing (control), PC12 (40 μm), MBC (1 μm), or calcium ionophore A23187 (2 μm) for 0, 10, 20, 30, 45, 60, 90, 120, or 180 min, and then fixed, permeabilized and incubated with a fluorescein isothiocyante (FITC)-labeled monoclonal antibody to phosphorylated protein, no consistent results were obtained using flow cytometry. Experiment 4 was designed to detect and classify sperm as hyperactive using novel software, minimum square binding ratio (MSBR). Control and CLC-treated stallion spermatozoa were incubated in MW or MW plus 5 mM procaine and then capacitated with PC12 (40 μm) or MBC (1 μm) for 15 min or 3 h. Sperm motility parameters were assessed using both the standard computer assisted sperm analysis (CASA) and the MSBR classification. Procaine treatment only, induced hyperactive motility in CLC-treated PC 12-capacitated sperm after 3 h incubation when using standard CASA analysis. MBC- treated spermatozoa exhibited the greatest changes in sperm motion parameters after 3 h. However, MSBR analysis indicated that neither PC 12 nor MBC-treated sperm were hyperactive at either time point, although all procaine supplemented samples had higher percentages of hyperactive sperm than control sperm (p < 0.05). Experiment 5 was designed to determine the effects of procaine supplementation on the acrosome reaction of stallion sperm treated with PC 12 or MBC. Stallion spermatozoa incubated in MW or MW plus 5 mM procaine were treated with nothing (control), PC12 (40 μm), or MBC (1 μm) for either 15 min or 3 h. The samples were then dual stained with FITC-PNA and propidium iodide (PI) and assessed by· flow cytometry. While PC 12 and MBC induced acrosome reactions in sperm, procaine had no effect on inducing acrosome reactions in stallion spermatozoa. Fertilization of bovine oocytes in vitro, with PC 12-(15 μM) treated stallion sperm resulted in higher cleavage rates (25% ± 3) than untreated sperm (9 % ± 4; p < 0.05). The ability of stallion spermatozoa to fertilize bovine oocytes following zona pellucida laser disruption was then addressed. Bovine oocytes given laser treatment exhibited lower cleavage rate when untreated or PC 12-treated sperm were co-incubated with them (3 and 4 % ± 2; p < 0.05) lhan zona intact oocytes inseminated with similarly treated sperm (9 vs. 30% ± 2; p < 0.05).
Keywords: Stallions -- Spermatozoa; Fertilization in vitro; Acrosome reaction